Components of Adaptive Augmented Reality Model for Heritage Mobile Application - Tenh, Hock Kuan; Shiratuddin, Norshuhada (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Adaptive augmented reality (AAR) is the latest concept of the augmented reality that responds and adapts to a real-time context and the characteristics of the users. This concept is said to provide adaptation of 3D augmented reality, better engagement and more emotional experience to the users. In AAR, the information is provided to the users through interaction tracking and sensor on the device. However, this technology is still in its infancy. Therefore, a study to explore positive ways of providing relevant information that can enhance user experience is urgently required. The objective of this paper is to identify the components of an AAR model for heritage mobile application. It is hypothesized that such model would enhance user experience and provide better engagement. Consequently, models from past studies on Augmented Reality, UX Design and storytelling are reviewed. Findings indicate that personalization and emotion are among the important components. Inclusion of these components seems to allow users to be more engaged and inspired to learn about the cultural heritage, hence enhances user experience.